Noise exposure at school and blood pressure in adolescents - Fadhilah Ihsani; Rafita Ramayati; Muhammad Ali; Rusdi Djas; Oke Rina Ramayani; Rosmayanti Siregar; Beatrix Siregar (Indonesian Pediatric Society, 2016)
Background The increasing prevalence of primary hypertension has motivated researchers to identify influencing factors, one of which is noise. There have been few studies on a relationships between noise exposure and blood pressure in children, and none have dealt exclusively with adolescents.Objective To assess for an association between noise exposure at school and blood pressure in adolescents. Methods To identify noisy and quiet schools, the mean noise levels of 192 senior high schools in Medan were measured using sound level meters. One noisy school and one quiet school were randomly selected for inclusion (mean noise levels of 68.2 and 53.8 dB, respectively). Students from both schools underwent blood pressure measurements by mercury sphygmomanometer. Their Body weights and heights were obtained for body mass index calculations. Subjects filled questionnaires and their parents were interviewed regarding history of illnesses.Results Of the 271 adolescents recruited, 136 (50.2%) were from the noisy school. Adolescents from the noisy school had higher mean systolic and diastolic blood pressures [121.6 (SD 13.87) mmHg and 71.1 (SD 8.15) mmHg, respectively], than those from the quiet school [111.8 (SD 12.61) mmHg and 63.8 (SD 8.05) mmHg, respectively]. After adjusting for other factors, noise had a significant, moderate, positive association with systolic and diastolic blood pressures [β = 0.452; B = 6.21 (95% CI 3.86-8.55) mmHg; and β = 0.473; B = 4.18 (95% CI 2.41 to 5.94) mmHg, respectively].Conclusion Adolescents from a noisy school have a greater risk of higher systolic and diastolic blood pressures than those from a quiet school.